STUDI KONSERVASI BANGUNAN CAGAR BUDAYA DI DALAM KAWASAN RENCANA PENGEMBANGAN PELABUHAN BEBAS SABANG - Albina Arahman; Mochammad Afifuddin; Safwan Yusuf (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Sabang city has many cultural heritage buildings that were built in 1880’s. These cultural heritage buildings are located around Sabang Bay. These cultural heritage buildings are not properly recorded and there is no detailed planning to preserve and to develope this cultural heritage. The development plan of Sabang free port, which has been set since 2000, requires adequate land and facilities. This development will certainly demerit the existence and drawback the rescue effort of heritage buildings within the free port development site. This research aims to obtain the potential value of the heritage buildings as well as to propose conservation action plan to link the existing heritage buildings to the regional development plan. The collected data was carried out by observation in the form of inventory activities. This study was carried out using a descriptive method. The building exposure both physically and non-physically was observed. Then, descriptive quantification was given in weighting of building values to determine the potential value of the investigated heritage building. This study reveals the buildings with a high value such as Mandiri Bank Building (NV Zeehaven de Kolen Station), Office of Drug Police Unit, Port Office (Harbormaster)/PT Telkom, Tikeng Hwi house (ex-shipping agent office) and Suka Ria Shops. Buildings with medium value are Milan Sports Shops, Riang Shop, and Asia Barber and friend. Finally, buildings in low value are Sabang Mini Market Shops, BNI warehouse and Murah Raya Shops.